2008
DOI: 10.1590/s0100-736x2008000600003
|View full text |Cite
|
Sign up to set email alerts
|

Intoxicação experimental com as folhas de Jatropha gossypifolia (Euphorbiaceae) em ovinos

Abstract: As folhas recém-colhidas de Jatropha gossypifolia (Euphorbiaceae) foram letais para ovinos em administrações únicas de 40g/kg. A dose de 5g/kg não causou sintomas de intoxicação; as doses intermediárias provocaram a morte de parte dos animais. A evolução da intoxicação foi de 6 a 22 dias. O quadro clínico-patológico nos ovinos experimentais era caracterizado por perturbações digestivas, pulmonares, cardíacas e ainda alterações regressivas leves somente evidenciadas através de exames histológicos, hepáticas e r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…The study of experimental poisoning in sheep showed that the intake of fresh plant leaves in a single dose of 40 g/kg was lethal to these animals [ 137 ]. The clinical and pathological picture in the experimental sheep was characterized by digestive, lung, and heart disturbances and also by slight regressive changes evidenced in hepatic and renal histological examinations [ 137 ].…”
Section: Toxicologymentioning
confidence: 99%
“…The study of experimental poisoning in sheep showed that the intake of fresh plant leaves in a single dose of 40 g/kg was lethal to these animals [ 137 ]. The clinical and pathological picture in the experimental sheep was characterized by digestive, lung, and heart disturbances and also by slight regressive changes evidenced in hepatic and renal histological examinations [ 137 ].…”
Section: Toxicologymentioning
confidence: 99%
“…Na dose de 40g/ Kg todos os ovinos submetidos ao ensaio morreram, sendo os sintomas princiais diminuição do apetite até anorexia, fezes pastosas até líquidas, respiração dispnéica, taquicardia, apatia, decúbito e morte (OLIVEIRA, et al, 2008).…”
Section: Jatropha Gossypifoliaunclassified
“…However, there are records of the use of Jatropha curcas as purgative by humans and animals causing intoxication (OLIVEIRA et al, 2008). The limitation of the use of this co-product as food is attributed to the presence of toxic, allergenic and anti-nutritional components (ABDALLA et al , 2008;MENDONÇA, 2010) such as curcina, diterpene esters (phorbol ester) and proteins with allergenic potential (OLIVEIRA; AKISUE, 2005).…”
Section: Introductionmentioning
confidence: 99%